A Logic Model for Planning, Implementing, and Evaluating a Student-Run Free Clinic - McAndrew, Rose; Kaskutas, Vicki (Journal of Student-Run Clinics, 2020)
Student-run free clinics (SRFCs) are an important part of the American healthcare system, providing free services to many individuals in need. Patients report improvements after care in an SRFC, and students develop skills requisite for practice. Current literature describes outcomes at SRFCs for patients and students but fails to provide a solid model to guide planning, implementation, and evaluation of SRFCs’ success. This paper presents the SRFC logic model, a contextually based model that is useful throughout the life of an SRFC. The SRFC logic model utilizes a backward design process for planning a new SRFC. The same five components examined in the planning process are performed in reverse order during the implementation and evaluation phases. The planning phase begins by identifying the impact that the SRFC hopes to make, followed by defining the measurable outcomes the SRFC expects to achieve. Outputs are projected to examine the reach of the SRFC. Specific activities to produce the desired output and outcomes are defined. Lastly, the inputs needed to complete the activities are identified. Implementation of the SRFC addresses the same components in a forward direction. Evaluation is performed iteratively, allowing for adjustments to ensure that the SRFC is achieving its targeted outcomes. The logic model described in this paper can be used across healthcare disciplines and settings to plan, implement, and evaluate an SRFC and to demonstrate its significance to all stakeholders.